BIOCOMPOSITE MATERIAL COMPRISING BEESWAX AND METHOD FOR OBTAINING BIOCOMPOSITE MATERIAL USING BEESWAX - Patent application

A biodegradable composite material using poly(lactic acid), diatomaceous earth, and beeswax addresses the need for environmentally friendly alternatives by enhancing processing and mechanical properties, suitable for industrial applications.

JP2025503816APending Publication Date: 2025-02-05POLITECHNIKA WARSZAWSKA +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024545217
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-27
Filing Date
2023-01-25
Publication Date
2025-02-05

AI Technical Summary

Technical Problem

Conventional polymer composite materials are not environmentally friendly and lack efficient processing characteristics, necessitating the development of biodegradable alternatives with improved mechanical and processing properties.

Method used

A composite material comprising biodegradable poly(lactic acid), diatomaceous earth, and beeswax is developed, where beeswax acts as an independent rheology factor to enhance processing characteristics and mechanical properties, replacing synthetic wax additives.

Benefits of technology

The composite material exhibits improved melt flow rate, mechanical strength, and resistance to environmental conditions, making it suitable for various industrial applications while being non-toxic and physiologically neutral.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503816000001_ABST
    Figure 2025503816000001_ABST
Patent Text Reader

Abstract

The present invention relates to biocomposite materials comprising beeswax and methods for producing biocomposite materials using beeswax, which can reduce the carbon footprint of composite materials by eliminating / replacing synthetic (petroleum-based) waxes used as processing additives.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a biocomposite material consisting of biodegradable poly(lactic acid), diatomaceous earth and beeswax, and a method for obtaining the composite material using beeswax. The use of beeswax to produce the biocomposite material is also disclosed. The use of beeswax allows the elimination of synthetic (petroleum-derived) waxes used as processing additives. [Background technology]

[0002] Composites are materials with a heterogeneous structure, consisting of at least two phases. Their combination results in a material with properties different from those of the initial individual components. In most cases, composites consist of two components: a structural element and a filler element, but sometimes additional components are used. The structural element, or the main component that constitutes the continuous phase, consolidates the filler fragments, allows the product to be properly shaped, and determines most of the physical and chemical properties of the material. The function of the dispersed phase is to improve certain properties of the material. Additional components are used to enhance the interaction between the matrix and the filler, thereby affecting the cohesion and homogeneity of the material. Typical composites are based on polymers such as styrene polymers, polycarbonates, thermoplastic polyesters, polypropylene, etc., and their production is not ecological.

[0003] In recent decades, traditional polymer composites for various applications have increasingly been replaced by composites obtained using renewable raw materials, called biocomposites.

[0004] The need to limit the discharge of plastic waste, to emphasize sustainable manufacturing methods, and to reduce energy consumption has led to a mainstream trend in the development of environmentally friendly polymers and polymer composites in recent years. Composites are materials that contain one or more phases of organic origin. The market for the production and sale of composites has been monitored for several years, contributing to the intensification and progress of research into their production and improvement. For these reasons, biopolymers obtained from natural resources are now replacing petroleum-based polymers. They can also contribute to reducing the carbon footprint of products. Among biopolyesters, polylactide (PLA) has gained a well-established position due to its processability, sustainable nature, and relatively low price.

[0005] A 2019 publication by Aguero A et al. presents an eco-friendly composite of poly(lactic acid) (PLA) and diatomaceous earth (DE), produced by extrusion followed by injection molding. DE was used as a filler. Several agents acting as compatibilizers / coupling agents, such as (3-glycidyloxypropyl)trimethoxysilane, epoxystyrene-acrylic oligomer, and maleated linseed oil, have been used to improve the interaction between the polymer and the filler. DE ensures a good elastic modulus upon stretching and produces a more brittle composite due to stress concentration phenomena. On the other hand, the compatibilizer contributes to improving the ductility, producing an eco-friendly material with sustainable mechanical properties. A 2020 publication by Dobrosielska et al. presents a novel composite of polylactide (PLA). It contains a natural filler produced from the shells (cell walls) of diatoms (frustum) that allows the modification of the matrix composed of PLA, and is produced by fused deposition modeling (3D printing). Their preparation is also described.

[0006] The WO2012106006A1 application discloses a biolaminate composite assembly including one or more layers of a biolaminate, at least one of which layers includes poly(lactic acid) and a natural wax, the wax being soy wax and constituting about 5% by weight of the biolaminate composite assembly.

[0007] A 2019 paper by Righetti et al. used a composite material consisting of 85% PLA, 10% by weight of the plasticizer tri-n-butyl acetyl citrate (ATBC), and 5% by weight of CaCO. 3 Biocomposites made from a polymer matrix containing PLA with subsequent addition of 20% by weight of potato pulp powder are described. To obtain wax-covered biocomposites based on PLA with potato pulp powder, non-ionic aqueous emulsions of commercial beeswax, carnauba wax or modified polypropylene wax were added to the pulp at a concentration of 5% w / v. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Patent Publication No. 2012 / 106006 (WO2012106006A1) [Non-patent literature]

[0009] [Non-Patent Document 1] Aguero A et al.; 2019. Effect of different compatibilizers on environmentally friendly composites from poly(lactic acid) and diatomaceous earth. Polymer Int. 68(5): 893-903 [Non-Patent Document 2] Dobrosielska et al.; 2020. Biogenic Composite Filaments Based on Polylactide and Diatomaceous Earth for 3D Printing. Materials; 13(20). 4632. [Non-Patent Document 3] Righetti MC. Cinelli P. Mallegni N. Massa CA. Aliotta L. Lazzeri A. Thermal. Mechanical. Viscoelastic and Morphological Properties of Poly(lactic acid) based Biocomposites with Potato Pulp Powder Treated with Waxes. Materials (Basel). 2019;12(6):990. Summary of the Invention

[0010] In connection with the search for alternatives to traditional polymer composites, this study obtained a composite material consisting exclusively of biodegradable poly(lactic acid), diatomaceous earth, and beeswax. The developed invention is a three-component material consisting exclusively of natural raw materials, namely a biopolymer, PLA, a natural bulking agent (diatomaceous earth), and beeswax.

[0011] The aim of the present invention is to improve the state of the art composites by using natural beeswax as an agent to improve the processing properties (melt flow rate) required for the manufacturing process of composites based on PLA and diatomaceous earth. The use of beeswax in the described composite system provides better rheological properties compared to the polyamide waxes commonly used in the processing industry. At the same time, beeswax is hypoallergenic and completely natural. In the present invention, the wax is an independent rheological factor that adjusts the viscosity of the two-component biocomposite with PLA and ensures a homogeneous structure.

[0012] The composite materials obtained with beeswax and manufactured using standard processing techniques have improved mechanical properties and processing capabilities, which not only provide a wide range of applications in many industrial sectors, but also answer the current trends related to the search for new solutions to replace traditional plastics. The waxes used are of biological origin and therefore have no carbon footprint, are non-toxic and physiologically neutral, so, unlike synthetic processing additives, they can be used in the manufacture of products that come into contact with food and human skin, animal feeding dishes, toys, household items, etc. Waxes as additives in the processing industry of plastics (biopolymer polylactide, PLA) increase the MFR (mass flow rate), and therefore the processing speed in injection, extrusion, blow molding, pressing or casting processes.

[0013] The present invention relates to a biocomposite of biodegradable poly(lactic acid) and diatomaceous earth, additionally comprising beeswax, wherein the content of diatomaceous earth is 2.5-15% of the mixture and the content of beeswax is 0.5-1% of the mixture.

[0014] The present invention also relates to a method for the preparation of a biocomposite, which comprises homogenizing poly(lactic acid) in the form of granules, crude diatomaceous earth, and beeswax at a temperature ranging from 180°C to 230°C, preferably from 205°C to 215°C, followed by pulverizing the components and extruding the pulverized product at a temperature ranging from 195°C to 210°C, followed by diluting the granules 1:1 with pure polylactide and conditioning the resulting composite at room temperature for 5 days and / or in a climatic chamber for 5 days with 10 heating-cooling cycles (+50°C, -10°C).

[0015] According to the present invention, the use of beeswax to obtain a biocomposite material is described, in which the wax (beeswax) becomes an independent rheological agent in a two-component system with poly(lactic acid). [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 shows the results of the melt flow rate of the granules after the injection process. [Diagram 2] FIG. 2 shows the tensile strength of the composites conditioned at room temperature. [Diagram 3] FIG. 3 shows the elongation at break of the composites conditioned at room temperature. [Figure 4] FIG. 4 shows the flexural strength (elastic modulus) test results for the composites conditioned at room temperature. [Diagram 5] FIG. 5 shows the flexural strength (maximum bending stress) test results for the composites conditioned at room temperature. [Figure 6] FIG. 6 shows the impact strength of the composites conditioned at room temperature. [Figure 7] FIG. 7 shows the tensile strength of the composites conditioned for 5 days in the climate chamber. [Figure 8] FIG. 8 shows the elongation at break of the composites conditioned for 5 days in the climate chamber. [Figure 9] FIG. 9 shows the flexural strength (elastic modulus) test results of composites conditioned for 5 days in a climate chamber. [Figure 10] FIG. 10 shows the flexural strength (maximum bending stress) test results of composites conditioned for 5 days in a climate chamber. [Figure 11] FIG. 11 shows the impact strength of the composites conditioned for 5 days in the climate chamber. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES

[0017] Example 1 Biocomposite Manufacturing The composite material was obtained by homogenizing the ingredients in the form of PLA4043D granules (Minnetonka, Minnesota, USA), crude diatomaceous earth (Perma Guard, Inc., Bountiful, UT 4010, USA), and beeswax at a temperature between 180°C and 230°C, preferably between 205°C and 215°C.

[0018] The wax used contains 100% natural beeswax and is the melted product of the 'honeycomb'. After the honey is extracted, the comb (a frame of dried honeycomb) is heated to melt the beeswax. Beeswax has a relatively low melting point, between 62°C and 64°C. The material used for the tests comes from the APIS Apiculture Cooperative in Lublin. The wax was standardised (in the form of 5 kg blocks) at a temperature of 210°C using a laboratory rolling mill (VM-150 / 280 Zamak Mercator).

[0019] Mixtures with different contents of diatomaceous earth (5%, 10%, 20%, 30%) with 1% and 2% beeswax or synthetic WTH-B wax or without any wax addition were obtained. The obtained systems were then pulverized using a plastic mill. Samples for strength testing were prepared by injection molding at temperatures between 195°C and 210°C by diluting the prepared mixtures 1:1 with pure PLA4043D to obtain systems with diatomaceous earth contents of 2.5%, 5%, 10% and 15% and beeswax contents of 0.5% or 1%. Using the same method, systems containing 0.5% synthetic WTH-B wax and systems not modified by wax addition were also prepared.

[0020]

number

[0021] Example 2 Testing of the melt flow rate (MFR. 210℃, load 2.16kg) of the produced biocomposite material.

[0022] The composite material for strength testing obtained by injection was pulverized in a plastic mill and dried at 60° C. for 24 hours before testing. The melt flow rate (MFR) measured for the unmodified PLA4043D was 8.47 g / 10 min. The addition of diatomaceous earth (DE) alone caused an increase in the MFR parameter, regardless of the concentration. At concentrations of 10% and 15%, there was an almost two-fold increase. The addition of synthetic WTH-B wax microbeads also caused an increase in the MFR, but only up to a maximum value of 14.9 g / 10 min at the highest concentration of diatomaceous earth. The increase was similar to that of the system without added wax, and no additional effect of the synthetic wax on the rheology of the composite in the molten (fluid) state was observed. On the contrary, at higher concentrations, higher MFR values ​​were observed for the composites without added wax. The addition of natural wax, regardless of its concentration (0.5%, 1%), caused a linear increase in the melt flow rate each time, reaching a value of 34.4 g / 10 min (more than four-fold increase) at a concentration of 1% additive (Figure 1, Table 1).

[0023] Table 1. Melt flow rate (MFR) of granules after injection process

[0024] [Table 1]

[0025] Example 3 Mechanical testing of the obtained biocomposites (breaking strength, flexural strength, impact strength). The biocomposites produced by the injection method were conditioned at room temperature or in a climate chamber for 5 days (heating-cooling cycles, −10°C, +50°C, 10 cycles, 6 h at −10°C and 6 h at +50°C for 12 h each cycle).

[0026] Both the addition of amorphous diatomaceous earth and the addition of waxes affect the mechanical properties of the composites produced, causing a decrease in parameters compared to pure PLA, which is associated with an increased brittleness of the material and is brought about precisely by the characteristics of diatomaceous earth.

[0027] The produced PLA / DE composites were characterized by higher values ​​of elongation at break and therefore lower brittleness than the wax-modified systems (Table 2). At a diatomaceous earth content of 2.5%, the elongation at break was 2.549% for the system without wax addition and 2.105% for the system with synthetic wax addition. However, it was 2.138% and 2.114% for the systems with 0.5% and 1% natural wax addition, respectively. The strength of the samples decreased with increasing DE concentration in the system (Figure 2). However, the decrease in material strength of the samples modified with beeswax was significantly smaller than that of the synthetic wax. In the case of beeswax additive, the maximum decrease in tensile strength (observed in the series according to concentration) was 2.45 MPa for the system with 0.5% beeswax content and 3.06 MPa for the 1% content. Meanwhile, in the case of synthetic wax, these values ​​increased to a maximum of 10.28 MPa.

[0028] The flexural strength modulus of unmodified PLA was 3.5 GPa (Table 3). Modification of PLA with diatomaceous earth caused an increase in the value of the parameter in each case, independent of the concentration. The addition of 0.5% synthetic wax WTH-B did not cause any significant change in the mechanical parameters (regardless of the concentration), but the addition of natural waxes significantly increased the value of the flexural modulus. A maximum value of 5.16 GPa was shown for the system with the highest concentration of DE (15%) and 1% beeswax addition (Figure 3). An increase of as much as 800 MPa was observed for the system with the highest concentration of DE, compared to modification with synthetic waxes.

[0029] The impact strength of pure PLA is 19.54 kJ / m 2 The addition of diatomaceous earth (2.5%) initially resulted in an increase in impact strength (20.76 kJ / m 2 ). Increasing the concentration of diatomaceous earth led to an increase in the brittleness of the material and a decrease in the impact strength. A similar trend was observed for the composites with the addition of natural wax (Figure 4). The highest value of impact strength at the highest concentration of diatomaceous earth (15%) was obtained for the sample modified with 0.5% beeswax content. Its impact strength was 16.21 kJ / m 2 at the same loading, whereas the synthetic wax modified system had a slightly lower value of 16.18 kJ / m 2In the case of pure diatomaceous earth without wax, 15.53 kJ / m 2 It was.

[0030] Conditioning the composites in a climatic chamber for 5 days did not result in any significant difference in the elongation at break and tensile strength values ​​of pure PLA. The systems modified with diatomaceous earth showed an improvement in the elongation parameters. The highest values ​​were observed for the systems with 1% natural wax addition, with values ​​up to 3.25% (an increase of about 70%) (Figure 5). At the same time, conditioning the composites in a climatic chamber did not significantly affect the flexural strength. All tested systems had similar values ​​of both flexural strength and maximum flexural stress (Figure 6).

[0031] Conditioning in a climatic chamber caused an increase in the impact strength of the composites. The best results were achieved by composites with 0.5% natural wax added, which had a maximum impact strength of 29.43 kJ / m, regardless of the concentration used. 2 (Figure 7).

[0032] Composites modified with diatomaceous earth and beeswax showed, in most cases, improved mechanical properties both in systems conditioned at room temperature and in systems exposed to the effects of adverse atmospheric conditions (high temperature, high humidity). The replacement of synthetic waxes with natural waxes not only allows the obtaining of fully biocomposites, but also allows the improvement of parameters such as processing parameters (higher MFR), thus facilitating the manufacturing process of the composites.

[0033] Table 2. Tensile strength - systems conditioned at room temperature (RT) and in a climate chamber (CC) for 5 days

[0034] [Table 2]

[0035] Table 3. Flexural strength - samples conditioned at room temperature (RT) and in a climate chamber (CC) for 5 days

[0036] [Table 3-1]

[0037] [Table 3-2]

[0038] Table 4. Impact strength - samples conditioned at room temperature (RT) and in a climate chamber (CC) for 5 days

[0039] [Table 4]

[0040] Literature: 1.Aguero A et al.; 2019. Effect of different compatibilizers on environmentally friendly composites from poly(lactic acid) and diatomaceous earth. Polymer Int. 68(5): 893-903 2.Dobrosielska et al.; 2020. Biogenic Composite Filaments Based on Polylactide and Diatomaceous Earth for 3D Printing. Materials; 13(20). 4632. 3.Righetti MC. Cinelli P. Mallegni N. Massa CA. Aliotta L. Lazzeri A. Thermal. Mechanical. Viscoelastic and Morphological Properties of Poly(lactic acid) based Biocomposites with Potato Pulp Powder Treated with Waxes. Materials (Basel). 2019;12(6):990.

Claims

1. A biocomposite material, comprising biodegradable poly(lactic acid) constituting a matrix of the composite material, diatomaceous earth constituting a filler, and beeswax constituting a rheological agent, the contents of each component being 84-97%, 2.5-15%, and 0.5-1%, respectively.

2. A method for producing the composite material of claim 1, comprising the steps of: a) homogenizing poly(lactic acid) in the form of granules, crude diatomaceous earth constituting 5%, 10%, 20% or 30% of the homogenizate, and beeswax constituting 1% or 2% of the homogenizate at a temperature ranging from 180°C to 230°C, preferably from 205°C to 215°C; b) finely grinding the ingredients; c) injecting the pulverized product at a temperature of 195°C to 210°C; d) diluting the pulverized product 1:1 with pure polylactide to obtain biocomposites with a diatomaceous earth content of 2.5%, 5%, 10% or 15% and a beeswax content of 0.5% or 1%; e) Conditioning the biocomposite for 5 days at room temperature and / or 5 days in a climate chamber with 10 heating-cooling cycles (6 hours at +50°C and 6 hours at -10°C for each cycle). Manufacturing methods for composite materials.

Citation Information

Patent Citations

  • Biolaminate composite assembly including polylactic acid and natural wax laminate layer, and related methods

    WO2012106006A1